Differences between prolonged weaning patients from medical and surgical intensive care units. Issue 9 (5th August 2016) - Bickenbach, J.; Marx, G.; Schmoor, C.; Lemmen, S.; Marx, N.; Dreher, M.
Abstract : Background: It is not clear whether patients entering a specialized, interdisciplinary weaning unit from surgical or medical intensive care units (ICU) distinguish substantially. The purpose of the present study was to assess differences in patients with prolonged weaning being referred from surgical and medical ICU. Methods: Data collected from April 2013 to April 2014 was conducted for retrospective analysis. Mortality rates, demographic data, clinical, and microbial differences in 150 patients with prolonged weaning were assessed (80 surgical and 70 medical). Results: Surgical ICU referrals tended to be older (70.7 ± 11.3 vs. 67.3 ± 12.3, P = 0.051) and had fewer underlying pulmonary diseases (45% vs. 60%, P = 0.067). Sodium values at the time of referral to the weaning unit were significantly higher in surgical (147.1 ± 9.6) vs. medical (141.3 ± 6.7 mmol/l) patients ( P < 0.001). Each 10‐unit increase in sodium at the time of referral to the weaning unit was associated with a 2.5‐day (95% CI −0.4, 5.4; P = 0.09) prolongation of stay in the weaning unit. Although significant differences in microbiological agents from tracheal aspiration were seen, the infection rate on the weaning unit was similar in both groups. There was no difference in weaning unit mortality between surgical and medical ICU patients (18% vs. 23%; P = 0.41). Conclusion: Few differences were found between patients being referred to a specialized weaning unit from surgical vs. medical ICUs. Besides differences in microbiological characteristics of tracheal secretions, there were also differences in sodium levels, which appear to influence on treatment duration.